Comparison of the efficacy of sitagliptin and glimepiride dose‐up in Japanese patients with type 2 diabetes poorly controlled by sitagliptin and glimepiride in combination. Issue 3 (22nd October 2013) - Shimoda, Seiya; Iwashita, Shinsuke; Sekigami, Taiji; Furukawa, Noboru; Matsuo, Yasuto; Ichimori, Shinji; Goto, Rieko; Maeda, Takako; Watanabe, Eiichiro; Kondo, Tatsuya; Matsumura, Takeshi; Motoshima, Hiroyuki; et al.
Abstract Aims/Introduction The goal of the study was to examine the effects of sitagliptin dose‐up or glimepiride dose‐up in Japanese patients with type 2 diabetes who were controlled inadequately by sitagliptin and glimepiride in combination. Materials and Methods A multicenter, prospective, randomized, open‐label study was carried out in 50 patients with type 2 diabetes treated with sitagliptin and low‐dose glimepiride. The patients were randomly assigned to receive the addition of 50 mg/day sitagliptin or 0.5 mg/day glimepiride. The primary end‐point was the percentage change in glycated hemoglobin (HbA1c). Results During a follow‐up period, the difference in the percentage changes in HbA1c between the two groups was not significant (P = 0.13). However, HbA1c was significantly decreased by glimepiride dose‐up (P < 0.01 vs baseline), but not by sitagliptin dose‐up (P = 0.74). Univariate linear regression analyses showed that the percentage change in HbA1c was significantly associated with the serum level of arachidonic acid (AA) in both groups. Conclusions There was no significant difference in the HbA1c‐lowering effects between the two groups. However, a significant HbA1c‐lowering effect from baseline of glimepiride dose‐up was found, and the AA level showed a negative correlation with the decrease in HbA1c in the sitagliptin dose‐up group, but a positive correlation in the glimepiride dose‐up group. These findings suggest that the AA level is associated with HbA1c reduction in response to dose‐up with these drugs in patients with type 2 diabetes in a combination therapy with sitagliptin and glimepiride. This trial was registered with UMIN (no. 000009544).